Knockout of integrin αvβ6 protects against renal inflammation in chronic kidney disease by reduction of pro-inflammatory macrophages - Changjian Zhu; Ruilin Zheng; Xu Han; Ziwen Tang; Feng Li; Xinrong Hu; Ruoni Lin; Jiani Shen; Qiaoqiao Pei; Rong Wang; Guangyan Wei; Zhenwei Peng; et al. (Cell Death and Disease, 2024)
Abstract Integrin αvβ6 holds promise as a therapeutic target for organ fibrosis, yet targeted therapies are hampered by concerns over inflammatory-related side effects. The role of αvβ6 in renal inflammation remains unknown, and clarifying this issue is crucial for αvβ6-targeted treatment of chronic kidney disease (CKD). Here, we revealed a remarkable positive correlation between overexpressed αvβ6 in proximal tubule cells (PTCs) and renal inflammation in CKD patients and mouse models. Notably, knockout of αvβ6 not only significantly alleviated renal fibrosis but also reduced inflammatory responses in mice, especially the infiltration of pro-inflammatory macrophages. Furthermore, conditional knockout of αvβ6 in PTCs in vivo and co-culture of PTCs with macrophages in vitro showed that depleting αvβ6 in PTCs suppressed the migration and pro-inflammatory differentiation of macrophages. Screening of macrophage activators showed that αvβ6 in PTCs activates macrophages via secreting IL-34. IL-34 produced by PTCs was significantly diminished by αvβ6 silencing, and reintroduction of IL-34 restored macrophage activities, while anti-IL-34 antibody restrained macrophage activities enhanced by αvβ6 overexpression. Moreover, RNA-sequencing of PTCs and verification experiments demonstrated that silencing αvβ6 in PTCs blocked hypoxia-stimulated IL-34 upregulation and secretion by inhibiting YAP expression, dephosphorylation, and nuclear translocation, which resulted in the activation of Hippo signaling. While application of a YAP agonist effectively recurred IL-34 production by PTCs, enhancing the subsequent macrophage migration and activation. Besides, reduced IL-34 expression and YAP activation were also observed in global or PTCs-specific αvβ6-deficient injured kidneys. Collectively, our research elucidates the pro-inflammatory function and YAP/IL-34/macrophage axis-mediated mechanism of αvβ6 in renal inflammation, providing a solid rationale for the use of αvβ6 inhibition to treat kidney inflammation and fibrosis.